This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: ln(1-t ) = Z-1 1-t dt = Z X n =0-t n dt = X n =0 Z-t n dt = X n =0-t n +1 n + 1 + C. Plugging in t = 0 gives 0 = ln(1-0) = X n =0 0 + C, so that C = 0. Putting it all together, weve so far discovered that ln(1-t ) = X n =0-t n +1 n + 1 . Finally, multiplying by t and integrating yields Z t ln(1-t ) dt = Z t X n =0-t n +1 n + 1 dt = Z X n =0-t n +2 n + 1 dt = X n =0 Z-t n +2 n + 1 dt = X n =0-t n +3 ( n + 1)( n + 3) + C. Finally, since the radius of convergence of our rst series ( n =0-t n ) was 1, and we only changed it in ways (integration, multiplication by t ) that dont aect the radius of convergence, our nal radius is also R = 1. Alternatively, you can check this using Ratio Test if you are so inclined. Im not....
View Full Document
- Spring '08
- Maclaurin Series